DOP19 Incidence and initial disease presentation of inflammatory bowel diseases in Denmark: findings from a Copenhagen IBD Inception Cohort Study (IBD Prognosis Study). (30th January 2023) - Attauabi, M; Madsen, G R; Wewer, A V; Bendtsen, F; Jakobsen, C; Dorn-Rasmussen, M; Malham, M; Theede, K; Bjerrum, J T; Boysen, T; Seidelin, J B; Burisch, J
Abstract: Background: The increasing incidence of inflammatory bowel diseases (IBD), encompassing ulcerative colitis (UC), Crohn's disease (CD), and unclassified IBD (IBD-U), in Denmark requires close surveillance. Therefore, we aimed to investigate their current incidence and initial disease presentation in a population-based inception cohort. Methods: IBD Prognosis Study is an ongoing prospective population-based inception cohort of patients diagnosed with UC, CD, or IBD-U between May 1 st, 2021, and May 1 st, 2023, according to the Copenhagen IBD Criteria within the well-defined geographical uptake area of Hvidovre University Hospital and Herlev University Hospital. This area has a catchment population of 1, 050, 000, corresponding to ~20% of the Danish population. The incidence rate is defined as the number of new cases between May 1 st, 2021, and October 31 st, 2022, divided by the total number of 100, 000 inhabitants covered in included sites per year during the same period. For the incidence calculations, pediatric-onset of IBD was defined as age < 19 years at diagnosis. However, for the clinical description, for the clinical presentation, the cut-off was <18 years. Results: As of October 31, 2022, a total of 219, 134, and 24 patients with adult-onset UC, CD, and unclassified IBD (IBD-U), respectively, has been included, corresponding to incidence rates of 13.9, 8.5, and 1.5 per 100, 000 adults per year. Further, 11, 16, and two patients with pediatric-onset UC, CD, and IBD-U were included, corresponding to 3.6, 6.3, and 0.7 per 100, 000 pediatric cases per year. Demographics and initial disease presentation are presented in Tables 1-2, initial disease burden and treatment patterns in Tables 3-4. Conclusion: The preliminary data from the ongoing prospective population-based cohort, IBD Prognosis Study, indicate that the incidence rates of adult-onset IBD appear stabilized, while that of pediatric-onset CD is increasing, when compared with data from before 2010. 1, 2 The study is ongoing and includes extensive and continuous examinations, including endoscopy, intestinal ultrasound investigations, magnetic resonance imaging of the small intestine and biliary and pancreatic ducts, patient-reported measures, and biobanking. As such, the cohort is expected to deliver essential knowledge on the mechanisms for the unpredictable course of IBD. 3 References: 1. Vind I et al. Am J Gastroenterol . 2006; doi:10.1111/j.1572-0241.2006.00552.x 2. Jakobsen C et al. Inflamm Bowel Dis . 2011; doi:10.1002/ibd.21654 3. Attauabi M et al. BMJ Open . 2022; doi:10.1136/bmjopen-2021-055779